Do community health workers perceive mechanisms associated with the success of community case management of malaria? A qualitative study from Burkina Faso. (January 2015) - Druetz, Thomas; Kadio, Kadidiatou; Haddad, Slim; Kouanda, Seni; Ridde, Valéry
Abstract: The use of community health workers to administer prompt treatments is gaining popularity in most sub-Saharan African countries. Their performance is a key challenge because it varies considerably, depending on the context, while being closely associated with the effectiveness of case management strategies. What determines community health workers' performance is still under debate. Based on a realist perspective, a systematic review recently hypothesized that several mechanisms are associated with good performance and successful community interventions. In order to empirically investigate this hypothesis and confront it with the reality, we conducted a study in Burkina Faso, where in 2010 health authorities have implemented a national program introducing community case management of malaria. The objective was to assess the presence of the mechanisms in community health workers, and explore the influence of contextual factors. In 2012, we conducted semi-structured interviews with 35 community health workers from a study area established in two similar health districts (Kaya and Zorgho). Results suggest that they perceive most of the mechanisms, except the sense of being valued by the health system and accountability to village members. Analysis shows that drug stock-outs and past experiences of community health workers simultaneously influence the presence of several mechanisms. The lack of integration between governmental and non-governmental interventions and the overall socio-economic deprivation, were also identified as influencing the mechanisms' presence. By focusing on community health workers' agency, this study puts the influence of the context back at the core of the performance debate and raises the question of their ability to perform well in scaled-up anti-malaria programs. Highlights: We investigated community health workers' perceptions of their work in Burkina Faso. They perceive most performance-related mechanisms except being valued by the health system. Their mechanisms' perception is highly influenced by contextual and implementation-related factors. Drug stock-outs and lack of integration between interventions are key barriers to performance. Community case management programs require strengthening of local health systems.